Online and Digital Education at Universities of Uzbekistan - L. S. Makhmutkhodjaeva (Открытое образование (Москва), 2021)
Purpose of the study. The digital turn in higher education and pedagogical technologies requires the use of a variety of teaching approaches and methods. The quarantine period in connection with the COVID-19 pandemic caused the need for a radical transformation of the higher education system, its new paradigm in a modern digital society. In such conditions, it becomes necessary to form a digital educational environment and many countries, including the Republic of Uzbekistan, have faced this task. Students need to develop skills in working with information, in particular, the use of information and communication technologies in the process of solving cognitive tasks and performing creative tasks in cognitive and educational activities. All these processes update the topic of the article and require an analysis of the experience of using electronic educational resources in the Republic of Uzbekistan.Materials and methods. The methodological basis of the research was the activity-oriented, personality-oriented, systemic, project-based and individually creative approaches. The analysis of the historiography of the problem showed: despite a significant number of studies in the field of application of various information technologies in historical research, there are still no works that would summarize data on working with electronic educational resources in the Republic of Uzbekistan. This article is an attempt to offer an analysis of the possibilities, as well as the main advantages of using electronic educational resources in teaching disciplines in higher education, using the example of Uzbekistan.Results. The article examines electronic resources for distance education that are present in the CIS countries, since online educational resources as a complex of various educational materials, for which gadgets are used, can improve the quality of education and diversify the forms of teaching. The author analyzes the conditions and prospects for the development of distance education in the Republic of Uzbekistan, notes a conceptual approach to educational digital platforms that contribute to improving the quality of education. The system of higher education of the Republic as well as the conditions and prospects for the development of distance education in the Republic of Uzbekistan are investigated. The author identifies the main trends in the modern online educational environment. In addition, the advantages and disadvantages of electronic educational resources have been identified. The article defines the strategic goals for the development of higher education in the Republic of Uzbekistan at a new stage of development, and also presents an analysis of Internet resources for distance education that are available in Uzbekistan. Conclusion. Thus, we come to the conclusion that in the current conditions, many countries are switching to digital and electronic means of education; the article shows the main Internet resources that contribute to the effectiveness of the system of professional training for bachelors, using the example of the Republic of Uzbekistan. The effectiveness, intensity, activation, individualization, and communicativeness of the educational process depend to a greater extent on how electronic resources are used, what tasks are solved during their use.